A Commentary on Telerehabilitation Services in Pakistan: Current Trends and Future Possibilities - Zeshan Zahid; Suleman Atique; Muhammad Hammad Saghir; Iftikhar Ali; Amna Shahid; Rehan Ali Malik (International Journal of Telerehabilitation)
A 2014 World Health Organization (WHO) study reported that almost 27 million people with disability live in Pakistan with fewer than one allied rehabilitation professional per 10,000 people. The current study sought to determine the attitudes toward telerehabilitation via a survey administered to 329 Pakistani rehabilitation professionals. Study results indicate that rehabilitation professionals in Pakistan are knowledgeable about telerehabilitation and Information and Communication Technology (ICT), and are receptive to employing telerehabilitation programs and applications. Therefore, we can infer that the future of telerehabilitation can be bright in Pakistan but requires the attention of policy makers and non-government organizations to launch an appropriate program nationwide. The authors suggest that a range of telerehabilitation services (e.g., consultation, assessment, and therapy) could alleviate the shortage of rehabilitation personnel in Pakistan.